Leadership Functionality In Organizing Events Of Unique Arts Academy - Lingesh Chandree, A/P Ramachandran. (Universiti Malaysia Sarawak (UNIMAS), 2018)
This research conducted to analysis the Leadership Functionality in Organizing Events of Unique Arts Academy. This research conducted with two objective which is to identify leadership functionality of Unique Arts Academy leader in organizing events and then to documenting leadership functionality in managing the events and activities by Unique Arts Academy leader. This research conducted using qualitative method based on Path-Goal Theory which is model of Leader Behaviors.